The Pecuniary Costs of Early School Leaving and Poor Basic Cognitive and Non-cognitive Skills - Giorgio Brunello; Lorenzo Rocco (Institute of Labor Economics (IZA), 2024)
We produce estimates of the pecuniary costs of inadequate investment in human capital for countries, macro regions and the world at large. These costs are borne by individuals (private costs), the government (fiscal costs), and society, which includes both individuals and the government (social costs). We estimate that, in 2030, the global annual private costs of having a share of children with less than basic skills at its 2021 value rather than at zero are equal to 9,154 billion 2015 dollars, or 17.1 percent of global GDP in 2030.
Keywords: I24; I25; 330; early school leaving; low basic skills; private; fiscal and social costs